Selfing and Drought-Stress Strategies Under Water Deficit for Two Herbaceous Species in the South American Andes - Ricote, Natalia; Bastias, Cristina C.; Valladares, Fernando; Pérez, Fernanda; Bozinovic, Francisco (Frontiers in Plant Science, 2019)
Angiosperms are highly diverse in their reproductive systems, including predominantly selfing, exclusive outcrossing, and mixed mating systems. Even though selfing can have negative consequences on natural populations, it has been proposed that plants having a predominantly selfing strategy are also associated with fast development strategies through time limitation mechanisms that allow them to complete their life cycle before the onset of severe drought. This relationship might be affected by the challenges imposed by global change, such as a decrease in pollinator availability and the earlier and more severe onset of droughts. In this work, our aim was to investigate whether selfing is correlated with a dehydration avoidance strategy, and how this could affect drought resistance and survival in two species with different types of selfing: pollinator-independent delayed selfing (Schizanthus grahamii) and pollinator-dependent selfing (Schizanthus hookeri), representing a gradient in selfing rates. We hypothesize that delayed selfing species and highly selfing populations will show “fast” plant traits whereas we will find no pattern in more outcrossed populations of the pollinator-dependent species. However, we predicted that high selfing populations would have lower survival rates when exposed to chronic drought early in their development since fast traits imply physiological compromises that will affect their drought survival. To evaluate these hypotheses, we characterized different physiological and morphological traits in response to two contrasting treatments (moist and dry) in a total of 6 populations of the two species. We found a relationship between the delayed selfing species and a dehydration avoidance strategy and also with low drought survival. Our work offers evidence to support the importance of abiotic factors, such as drought, on the possible variation in selfing rates on natural populations, and the effect that this mating system could have in their ability to face new environmental conditions such as those imposed by climate change.